2016
DOI: 10.1039/c5ta09166g
|View full text |Cite
|
Sign up to set email alerts
|

“Nanotraps” in porous electrospun fibers for effective removal of lead(ii) in water

Abstract: In this report, we demonstrated a synthetic strategy for the effective removal of Pb2+in water by creating stable “nanotraps” in electrospun porous cellulose acetate fibers encapsulated with dithiothreitol capped gold nanoclusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…received a great deal of attention owing to their high surface area, very light-weight, nano-porous nature, and flexibility in specific physical and chemical functionalization [13][14][15]. Thereby, electrospun fibers and their webs are very promising candidates for membranes/filters and environmental applications [16][17][18][19][20]. For example, electrospun webs were also used as immobilization matrix for living microorganism for remediation of waste water [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…received a great deal of attention owing to their high surface area, very light-weight, nano-porous nature, and flexibility in specific physical and chemical functionalization [13][14][15]. Thereby, electrospun fibers and their webs are very promising candidates for membranes/filters and environmental applications [16][17][18][19][20]. For example, electrospun webs were also used as immobilization matrix for living microorganism for remediation of waste water [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the continuous development of global industry and agriculture have caused aggravated pollution from heavy metals and organic dyes; these compounds affect human and animal health because of their complex composition, photolysis resistance, oxidation resistance, and unbiodegradable nature . The quick and efficient removal of toxic dyes and metal ions to wastewater discharge standards remains a challenge for scientific research personnel . Over the past few decades, a large number of adsorption techniques have been developed for the adsorption and enrichment of some metal ions (Pd, Cu, Cr, Hg, and Pb) and organic dyes; among these, amidoximated polyacrylonitrile (AOPAN) solution chelating nanofibers have been demonstrated to the most promising candidates because of their large specific surface area, high speed of exchange, short regeneration time, and easy elution properties …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The quick and efficient removal of toxic dyes and metal ions to wastewater discharge standards remains a challenge for scientific research personnel. [6][7][8][9] Over the past few decades, a large number of adsorption techniques have been developed for the adsorption and enrichment of some metal ions (Pd, Cu, Cr, Hg, and Pb) and organic dyes [10][11][12][13][14] ; among these, amidoximated polyacrylonitrile (AOPAN) solution chelating nanofibers have been demonstrated to the most promising candidates because of their large specific surface area, high speed of exchange, short regeneration time, and easy elution properties. [15][16][17][18][19][20][21][22][23] Now, most of the preparation work for amidoxime-based chelate nanofibers is done through chelating modification with hydroxylamine hydrochloride after the synthesis of polyacrylonitrile (PAN) nanofiber mats by an electrospinning method.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the additional functionalities of metal (Pd NC) and metal oxide (ZnO NP) NP can be introduced onto the nanofibrous mats via NH 2and -alkoxy/ hydroxyl features for catalytic reduction and photocatalytic applications in addition to the fluorescent feature. In our previous studies, we have shown that electrospun nanofibrous mats of cellulose acetate, 13 polycaprolactone, 14 polysulfone, 15 and Nylon 6,6 16 can be surface-functionalized with various nanostructures (e.g., gold nanoclusters, 13,14 ZnO 15,16 ) for applications such as heavy-metal removal, 13 sensing, 14 and photocatalysis. 15,16 It is also possible to surface-functionalize many other electrospun NF of polymers or polymeric composites.…”
Section: Introductionmentioning
confidence: 99%